A generic conspectus of the Microdontinae (Diptera: Syrphidae) with the description of two new genera from Africa and China - Cheng, Xin-Yue; Thompson, F. Christian (Zootaxa, 2008)
A new genus and species of flower flies is described from China (Furcantenna Cheng, type F. yangi Cheng). Another new genus is proposed for the Afrotropical species incorrectly placed in Ceratophya, Afromicrodon Thompson, type Microdon johannae Doesburg. A key is provided to the groups of the Subfamily Microdontinae, along with a checklist of genus-group names proposed within the subfamily and nomenclatural and taxonomic notes on them.